Japanese literature on film the second teaching module in the series Japanese society through film. - Japan Society (New York, N.Y.) (New York : Japan Society, 1989)
Three films that are both visually effective renderings of three outstanding works of Japanese literature and effective films in their own right.
[pt.1] Double suicide (105 min.)-- [pt.2] Snow country (134 min.) --[pt. 3] The face of another (121 min.)
VHS format
"Janus film presentation."
Keywords: Feature films